White blood cells in polish athletes of various sports disciplines - Orysiak, J.; Witek, K.; Zmijewski, P.; Gajewski, J. (Biology of Sport, 2012)
The purpose of this study was to examine the diversity of white blood cell (WBC) counts and their subsets (neutrophils, lymphocytes and monocytes) among competitive athletes of different sports disciplines. The blood samples were collected from 608 healthy, medically examined athletes (181 females and 427 males) aged 20.1 ± 5.1 years, who represented five sport disciplines: canoeing, judo, rowing, swimming and volleyball. All blood samples were taken from the antecubital vein in the morning, after overnight fasting, in a seated position. Haematological analyses were conducted using a haematology analyser (ADVIA 120, Siemens). Neutropenia (defined as neutrophil count <2.0 · 109·L-1) was found in athletes of both sexes in each discipline. There was no incident of lymphopenia (defined as a lymphocyte count <1.0 · 109·L-1). Monocytopenia (defined as a monocyte count <0.2 · 109·L-1) was seen only in male athletes, except judo athletes. Differences in WBC and their subset counts were related to sport disciplines: in volleyball players WBC counts were significantly higher than in athletes of canoeing and rowing (in females); neutrophil counts were the lowest in swimming athletes; lymphocyte counts were lower in athletes of canoeing than in volleyball and swimming, but only in females; monocyte counts were lower in athletes of canoeing than swimming (in females) and judo (in males). In women, counts of neutrophils were greater and counts of monocytes were smaller than in men. It seems that prevalence of neutropenia and monocytopenia and differences in WBC counts and their subsets among disciplines could be related to the adaptive response to physical exercise.